2020
DOI: 10.1002/jbmr.4234
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Studies Reveal Novel Locus With Sex-/Therapy-Specific Fracture Risk Effects in Childhood Cancer Survivors

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Even though the evidence is currently very limited, genetics also seems to influence bone density in children with cancer. Te Winkel et al observed that variations in genes involved in folate metabolism negatively affect bone mass density in ALL patients at diagnosis [ 61 ], as well as the finding that a polymorphism of corticotrophin-releasing hormone receptor-1 gene is related to low bone density in male ALL survivors [ 6 ]. Furthermore, in 2020, Im and collaborators performed genome-wide association studies of fracture risk after cancer diagnosis in patients from the Childhood Cancer Survivor Study (CCSS), identifying a genetic locus (HAGHL, 16p13.3) for fracture risk [ 6 ].…”
Section: Physiopathology Of Osteoporosis In Ccs: General Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the evidence is currently very limited, genetics also seems to influence bone density in children with cancer. Te Winkel et al observed that variations in genes involved in folate metabolism negatively affect bone mass density in ALL patients at diagnosis [ 61 ], as well as the finding that a polymorphism of corticotrophin-releasing hormone receptor-1 gene is related to low bone density in male ALL survivors [ 6 ]. Furthermore, in 2020, Im and collaborators performed genome-wide association studies of fracture risk after cancer diagnosis in patients from the Childhood Cancer Survivor Study (CCSS), identifying a genetic locus (HAGHL, 16p13.3) for fracture risk [ 6 ].…”
Section: Physiopathology Of Osteoporosis In Ccs: General Risk Factorsmentioning
confidence: 99%
“…Te Winkel et al observed that variations in genes involved in folate metabolism negatively affect bone mass density in ALL patients at diagnosis [ 61 ], as well as the finding that a polymorphism of corticotrophin-releasing hormone receptor-1 gene is related to low bone density in male ALL survivors [ 6 ]. Furthermore, in 2020, Im and collaborators performed genome-wide association studies of fracture risk after cancer diagnosis in patients from the Childhood Cancer Survivor Study (CCSS), identifying a genetic locus (HAGHL, 16p13.3) for fracture risk [ 6 ]. A few years earlier, it was demonstrated by multivariate analyses that CCS carrying SNPs in the ESR1 (estrogen receptor type 1) or LRP5 (low-density lipoprotein receptor) genes had an impairment in bone mass at an early adult age [ 62 ].…”
Section: Physiopathology Of Osteoporosis In Ccs: General Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects put survivors at increased risk of failure to achieve potential peak bone mass and increase their fracture vulnerability in adulthood (59). The prevalence of low bone mineral density (BMD) indicates that osteoporosis occurs in almost 10% of cancer survivors with a median age of 32 years, the exact prevalence of osteoporosis among adult Americans aged 60 to 80 (60). Progression into osteonecrosis can be symptomatic, characterized by severe pain, joint damage, and articular collapse, or remain asymptomatic (61).…”
Section: Bone Toxicitymentioning
confidence: 99%